RESISTING THE PANDEMIC FROM THE MARGINS OF THE SCHOOL SYSTEM: THE CASE OF HIGH SCHOOL N° 60 IN GREATER RESISTENCIA - Marcelo A. Graciosi Barrios (Universidad Nacional del Nordeste, 2021)
This paper aims to problematize the experience undergone by teachers and students at a High School in Resistencia (capital city of the province of Chaco in Argentina) to face the COVID-19 pandemic. The analysis is done through analytical concepts from historical materialism and contemporary authors from both critical sociology and critical pedagogy. The specific objective is to analyze the impact of the pandemic and Mandatory Preventive Social Isolation, which implied school closures in 2020, on the pedagogical practices of a high school, observing the correlation between institutional strategies and the students and their families practices. We acknowledge that the particular case analyzed here- that of Angel Vicente Peñaloza High School N°60 - is similar to that of a large number of high schools in our country and in Chaco, historically characterized by social vulnerability situations.